Assessing the ecological status of seagrasses using morphology, biochemical descriptors and microbial community analyses. A study in Halophila stipulacea (Forsk.) Aschers meadows in the northern Red Sea. (January 2016) - Mejia, Astrid Y.; Rotini, Alice; Lacasella, Federica; Bookman, Revital; Thaller, Maria Cristina; Shem-Tov, Rachamim; Winters, Gidon; Migliore, Luciana
Highlights: A new integrated approach is proposed to assess the ecological status of seagrasses. Morphological and physiological descriptors were coupled with epiphytic microbiome. 454 pyrosequencing was used to study seagrass epiphytic microbiome. Descriptors highlighted ecological differences among meadows at small spatial scales. Microbial community is proposed as a putative descriptor for seagrass meadows. Abstract: Seagrasses are one of the most valuable marine ecosystems on earth, yet they are declining worldwide at alarming rates. With most of seagrass monitoring based on long term responses to environmental pressures, there is growing interest in developing alternative diagnostic tools that more effectively identify changes in seagrass ecological status at an early stage. Besides morphological indicators, functional and biochemical descriptors may provide a good understanding of plant's responses to environmental changes. Moreover, the epiphytic microbial communities of seagrasses may also shift in response to changes in environmental conditions, although these have been seldom used as a descriptor of environmental change. In this study three Halophila stipulacea (Forsk.) Aschers meadows, found in the Gulf of Aqaba (northern Red Sea), were characterized using an integrated approach to highlight possible differences in the meadows ecological status. Plant descriptors, including leaves morphometrics (leaf size, leaf number/plant, leaves with lost apex), photosynthetic pigments (Chlorophylls, Carotenoids) and total phenols contents, were investigated and coupled with the plants' epiphytic microbial community structure and composition, studied using pyrosequencing. The entire suite of descriptors highlighted differences among the meadows ecological status based on changes in plants' morphology and biochemistry, and their associated microbial communities, in response to the different environmental conditions (water column turbidity, seawater and sediment nutrients) and the geomorphological features (bottom slope, granulometry) of the stations. Leaf morphology and photosynthetic pigment content were modulated in H. stipulacea in response to light availability and hydrodynamics in the Gulf of Aqaba. The highest leaf surface area and photosynthetic pigment contents were observed at the lowest irradiance and hydrodynamics/granulometry among stations. Total phenol content showed differences among stations with increasing concentrations from north to south. The microbial communities showed differences among stations and plant compartments, with high incidence of Gammaproteobacteria and Bacteroidetes in light limiting conditions, while Cyanobacteria and Rhodobacteraceae thrived in conditions of high light availability and hydrodynamics. The mutual response of the seagrass plants and the microbial communities provided evidence of their functional relationship, which undoubtedly needs further investigation. To the best of our knowledge, this is the first time that such descriptors have been used in an integrated approach. We provide evidence of their effectiveness in discriminating seagrass ecological status, even at small spatial scales. This work constitutes a new approach to the assessment of seagrasses and a stepping stone in the application of microbial communities as a putative marker in a changing environment.